Réponses

2014-10-09T11:52:37+02:00
A) (x-(-2-√3))(x-(-2+√3))=x²-(-2+√3)x-(-2-√3)x+(-2-√3)(-2+√3)
(x-(-2-√3))(x-(-2+√3))=x²+4x-√3x+√3x+(-2)²-3=x²+4x+1
Donc f(x)=(x-(-2-√3))(x-(-2+√3))

b) f(x)=x²+4x+1=x²+4x+4-4+1=(x+2)²-3

c) f(x)=0
On utilise la forme factorisée :
(x-(-2-√3))(x-(-2+√3))=0
⇔ (x-(-2-√3))=0 ou (x-(-2+√3))=0
⇔x=-2-√3 ou x=-2+√3

f(x)=1
On utilise la forme développée :
x²+4x+1=1
⇔x²+4x=0
⇔x(x+4)=0
⇔x=0 ou x+4=0
⇔x=0 ou x=-4

f(x)=-3
On utilise la forme canonique :
(x+2)²-3=-3
⇔(x+2)²=0
⇔x+2=0
⇔x=-2

f(x)- (x-(-2-√3))=0
On utilise la forme factorisée
(x-(-2-√3))(x-(-2+√3))-(x-(-2-√3))=(x-(-2-√3))((x-(-2+√3))-1)
=(x-(-2-√3))(x-(-1+√3))
(x-(-2-√3))(x-(-1+√3))=0
⇔(x-(-2-√3))=0 ou (x-(-1+√3))=0
⇔x=-2-√3 ou x=-1+√3